Brand Image and Product Quality on Customer Loyalty (Survey in Cekeran Midun) - Minar, Demsi; Safitri, Anindia (TRIKONOMIKA, 2017)
The purpose of this research is to (1) know customer responses to brand image, product quality, and customer loyalty of Cekeran Midun, (2) know how big the influence of brand image and product quality on customer loyalty are. The methods used are descriptive and verificative analysis. Data were primary and secondary data. Primary data was obtained from questionnaires distributed to 87 customers in Cekeran Midun Cikutra branch, Bandung. Secondary data was obtained from literature texts, journals and other sources that fit the topic of research. The result of analysis and discussion showed that Cekeran Midun Bandung applied brand image in 4 forms namely, recognition, reputation, affinity and domain. Cekeran Midun also implemented 8 forms of product quality i.e. performance, durability, conformance to specifications, features, reliability, aesthetics, perceived quality and serviceability. The influence of brand image and product quality on customer loyalty was 23.32%.